(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Estimation of the age of an individual from the appearance and the fusion of the ossification centers is considered as a reasonable well accepted method in the field of medical and legal professions. Age estimation is essential during employment, marriage, fixation of criminal responsibility, judicial punishment, exercise of adult franchise and many other purposes. Bony age can be determine by the study of ossification centers of long bones through the appearance and fusion of epiphysis with diaphysis. The challenges during estimation of bony age are varying from place to place depending on geographic terrain, climatic, dietetic, hereditary, disease and other factor. So this study aimed to look out the status of fusion of ossification centers at the lower end of humerus for estimation of age among girls in Chattogram. Material and methods: This cross sectional observational study was performed in the period of July 2018 to June 2019on normal healthy student of 12 to 20 year age from the Prabartak School and College, Chattogram and Chittagong Medical College, Chattogram. The students (50 girls) were taken as subject and they were divided in eight groups according to their age. X-ray of the right elbow joint of each and every subjects were taken in antero-posterior and lateral view. The x-ray films were studied radiologicallyand interpreted to estimate the age byunion of ossification centers. Results: The average age of epiphyseal union in Chattogram was found as follows:Fusion of lateral epicondyle with capitulum in girls at 12-13 years. Fusion of capitulum withtrochlea in girlsat 12-13 years. Fusion of distal conjoint epiphyses with shaft in girls at 12-13 years. Fusion of medial epicondyle with shaft in girls at 13-14 years. Conclusion: In general the union of the ossification centers occurwithin 12-14 years in girls. JCMCTA 2021 ; 32 (2) : 100-104